Seismic performance of controlled spine frames with energy-dissipating members. (November 2015) - Takeuchi, T.; Chen, X.; Matsui, R.
Abstract: Recently, various controlled rocking systems have been proposed in seismic design to prevent damage concentration and to achieve self-centering against a wide range of input ground motion intensities. However, several obstacles must be overcome before these systems can be applied to actual buildings; for example, the requirement for large, self-centering post-tensioned strands and special treatment at uplift column bases must be addressed. This paper proposes a non-uplifting spine frame system with energy-dissipating members without post-tensioned strands, its self-centering function is achieved by envelope elastic-moment frames. The system is applied to an actual building constructed in Japan. Conventional shear damper and uplifting rocking systems with post-tensioned strands developed in prior studies are also applied to the same building structures, and the performances of the three systems, including damage distribution, energy dissipation, self-centering, robustness against severe earthquakes, and irregular stiffness, are compared and discussed through numerical simulations based on practical design criteria. Highlights: A controlled spine frame system is proposed and applied to an actual building. Comparable structures using various spine frame systems are designed. Seismic performance of the systems are compared by nonlinear dynamic analysis. Ultimate state of the proposed system is validated by IDA. Robustness against irregular stiffness of the proposed system is confirmed.